Critical Issue Bibliography (CRIB) Sheet Distance Education. - ERIC Clearinghouse on Higher Education, Washington, DC.; ERIC Clearinghouse on Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
This Critical Issue Bibliography (CRIB) Sheet focuses on distance education in higher education. Included are citations for some of the most recent ERIC literature in the field. Citations are grouped into: (1) Initial Steps (Directories); (2) Accreditation; (3) Challenges and Innovations; (4) Curriculum; (5) Institutional Applications; (6) Instructional Design and Technology; (7) Library Support for Distance Education Students; (8) Studies and National Surveys; and (9) Internet Resources. The bibliography contains 46 citations in the ERIC database and 5 Internet citations. (SLD)
Availability: For full text: http://www.eriche.org.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accreditation (Institutions); Annotated Bibliographies; Curriculum; Distance Education; Educational Innovation; Educational Technology; Higher Education; Instructional Design; ERIC Publications; Reference Materials, Bibliographies